THE EFFECT OF DIFFERENT REARING CONTAINERS COLORS ON THE COLOR BRIGHTNESS OF THE BARBIR FISH (Puntius conchonius) - Nabil Juwatiar Saifullah; Rosidah Rosidah; Subiyanto Subiyanto; Iskandar Iskandar (AQUASAINS, 2023)
This study aims to to determine the container color that is effective in increasing the brightness of the color of Barbir fish (Puntius conchonius). The research was carried out from June to August 2022 at the Aquatic Animal Physiology Laboratory of the Faculty of Fisheries and Marine Sciences, Padjadjaran University. This study used a complete randomized block design (RAL) experimental method with five treatments and three replications. The treatment consisted of five treatments namely control A (colorless container), blue container (B), yellow (C), Green (D) and orange (E). The treatment is given for 60 days. Parameters observed include absolute length and weight growth, color brightness, survival rate and water quality (temperature, DO and pH). The results showed that the growth parameters with the highest value obtained in the orange background color treatment (treatment E, including the growth of absolute length of 0,27 ± 0,076 cm and the growth of absolute weight of 0,12 ± 0,014 g, as well as parameters of color brightness with an increase in color score in Toca color finder (TCF) reached 1.5 on the body; 1,8 on the serip chest; and 1,6 on the tail. The value of water quality parameters are in normal conditions (temperature ranges from 24,2-28oC; DO ranges from 5,8-8,5 mg/l; and pH ranges from 6,89-7,62) so that both the survival rate of Barbir fish that is equal to 100%.Keywords: Puntius conchonius, container, background color, color brightness level, Orange